Religion, law, and freedom : a global perspective - Thierstein, Joel, 1961-; Kamalipour, Yahya R. (Westport, Conn. : Praeger, 2000)
Religion, Law, and Freedom: A Global Perspective introduces readers to diverse perspectives on the interplay of religion, law, and communications freedom in different cultures around the world. Through discussion and analysis of the religious mores and cultural values that a nation adheres to, a greater understanding of that nation, its laws, and its freedoms can be cultivated. Rather than suggesting that harmony can be achieved without conflict, the essays in this volume seek to present the reader with a variety of perspectives from which to view and understand the relationships among religion, law, and freedom in various cultures. This multifaceted analysis, therefore, helps readers draw their own conclusions as to the best way to resolve cultural conflict brought about by the growing global community. The book consists of fifteen chapters, authored or coauthored by 17 international scholars representing China, Germany, Israel, Iran, Japan, Latvia, Nigeria, Singapore, the United Kingdom, and the United States. The chapters are organized into four parts: Perspectives on Eastern and Western Religions; Press Freedom in Religious and Secular Societies; Journalism, Advertising, and Ethical Issues; and Religion, Politics, Media, and Human Rights. This important contribution will especially appeal to researchers and students in such fields as mass communications, legal studies, cultural studies, political science, religion, intercultural communications, international communications, and journalism.
Journalism, advertising, and ethical issues. Professional ethics and sociopolitical mobilization of Muslim journalists : a study of communication, ethics, and the Islamic tradition / Hamid Mowlana -- Confucian conflicts in Singaporean advertising : a case study of the "wonder bra" campaign / Linda K. Fuller. Religion, politics, media, and human rights. When size does matter : how church size determines media coverage of religion / Michael J. Breen -- Transcultural communication and the antimony between freedom and religion : a comparison of media responses to the Rushdie affair in Germany and the Middle East / Kai Hafez -- Japanese media, religion, and the law / Dan Tinianow -- Economic liberalization and political conservatism as reflected in China's media development (1978-present) / Guo Ke -- Faith in human rights : human rights in faith / Nazila Ghanea-Hercock.
Includes bibliographical references (pages 227-228) and index.
Print version record.
Keywords: Religion and law; Freedom of information; RELIGION -- Comparative Religion; Freedom of information; Religion and law; Electronic books; Electronic book